ANALYSIS OF THE FACTORS INFLUENCING THE SUCCESS OF STUDENT INTERNATIONAL PLACEMENT IN COMPANIES: A CASE STUDY AT INSTITUT TEKNOLOGI BISNIS AAS INDONESIA - Budiyono Budiyono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Placement of student internships in companies is an important component of higher education to prepare students for the world of work. The purpose of this study was to analyze the factors that influence the success of student internship placements in companies at Institut Teknologi Bisnis AAS Indonesia. The research method used is a qualitative and quantitative approach by collecting data through surveys, in-depth interviews, and focus group discussions. The research findings indicate that the suitability of the study program with the company's needs, supervisory support, effective communication, an inclusive work environment, and student satisfaction are important factors influencing the success of internship placements. The recommendations put forward include strengthening cooperation with companies, provide comprehensive guidance and orientation, improve communication and collaboration, create an inclusive work environment, and pay attention to student satisfaction. It is hoped that the results of this research can contribute to increasing the success of student internship placements in companies and improving the internship program at Institut Teknologi Bisnis AAS Indonesia. Keywords: factors, success, apprenticeship, company